2022
DOI: 10.1002/mco2.188
|View full text |Cite
|
Sign up to set email alerts
|

Mixed formulation of mRNA and protein‐based COVID‐19 vaccines triggered superior neutralizing antibody responses

Abstract: Integrating different types of vaccines into a singular immunization regimen is an effective and accessible approach to strengthen and broaden the immunogenicity of existing coronavirus disease 2019 (COVID‐19) vaccine candidates. To optimize the immunization strategy of the novel mRNA‐based vaccine and recombinant protein subunit vaccine that attracted much attention in COVID‐19 vaccine development, we evaluated the immunogenicity of different combined regimens with the mRNA vaccine (RNA‐RBD) and protein subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Currently, there is substantial evidence supporting that heterologous immunization can provide effective boosting; it has also been shown that mRNA and protein heterologous vaccination can improve the broad spectrum of produced antibodies [ 27 ]. Our study demonstrated that although the homologous mRNA groups exhibited the highest peak level of antibodies, after a slow decay of seven months, antibody levels in the heterologous groups reached a level more comparable to that of the homologous mRNA groups, particularly evident when tested against the Delta and Omicron strains.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is substantial evidence supporting that heterologous immunization can provide effective boosting; it has also been shown that mRNA and protein heterologous vaccination can improve the broad spectrum of produced antibodies [ 27 ]. Our study demonstrated that although the homologous mRNA groups exhibited the highest peak level of antibodies, after a slow decay of seven months, antibody levels in the heterologous groups reached a level more comparable to that of the homologous mRNA groups, particularly evident when tested against the Delta and Omicron strains.…”
Section: Discussionmentioning
confidence: 99%